Islamic banking business in Malaysia: the regulatory aspects - Trakic, Adnan; Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2012)
This chapter discusses the regulatory aspects of the Islamic Banking business in Malaysia with reference to the various legislation promulgated by the Malaysian Parliament and other subsidiary legislation enforced on the said topic.